The role of Indonesian as a communication tool in learning - Meylani, Aulia (Institute of Education and Social Research, 2024)
Language is the most important component in human life. Humans would not be able to continue their lives properly and regularly without language. They cannot interact easily and well if they do not master each other's language and in the absence of continuity they are also unable to capture the mental expressions or desires expressed by their communication partners. This also causes separation and a lack of emotional connection with each other. Language is the most effective communication tool in conveying messages, thoughts, feelings, goals to other people and makes it possible to create cooperation between people. So that the role of language becomes very dominant in various daily human activities. The aim of this research is to describe things related to Indonesian as a communication tool in learning. The method used in this research is the literature review method, data is collected from relevant library data. The results of this research and discussion are to explain language as a communication tool which includes discussing the function of language as a tool of human communication. Humans are social creatures who interact, cooperate and establish social contacts in society. Language allows humans to form social groups to fulfill their need to live together.